2012
DOI: 10.3109/15419061.2012.690792
|View full text |Cite
|
Sign up to set email alerts
|

Intercellular calcium waves in primary cultured rat mesenteric smooth muscle cells are mediated by Connexin43

Abstract: Intercellular Ca2 + wave propagation between vascular smooth muscle cells (SMCs) is associated with the propagation of contraction along the vessel. Here, we characterize the involvement of gap junctions (GJs) in Ca2 + wave propagation between SMCs at the cellular level. Gap junctional communication was assessed by the propagation of intercellular Ca2 + waves and the transfer of Lucifer Yellow in A7r5 cells, primary rat mesenteric SMCs (pSMCs), and 6B5N cells, a clone of A7r5 cells expressing higher connexin43… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 42 publications
2
9
0
Order By: Relevance
“…The fact that gap-junctional communication is required for contractile wave propagation/generation is consistent with previous work on Ca 2þ communication in smooth muscle cell cultures [14,32] and adult gut motility [33]. Other small molecules that diffuse through gap junctions, like ATP, may play a role in the propagation of the calcium wave [31,34].…”
Section: Discussionsupporting
confidence: 89%
“…The fact that gap-junctional communication is required for contractile wave propagation/generation is consistent with previous work on Ca 2þ communication in smooth muscle cell cultures [14,32] and adult gut motility [33]. Other small molecules that diffuse through gap junctions, like ATP, may play a role in the propagation of the calcium wave [31,34].…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies confirmed that intracellular Ca 2+ concentration regulates the permeability of gap junctions composed of Cx43 (39,40). Increased abundance of intracellular Ca 2+ can activate calcium-dependent proteolytic enzymes (calpains), which can degrade a variety of proteins, and change cell structure and function (41).…”
Section: Discussionmentioning
confidence: 87%
“…The potential vasculoprotective effect of Cx43 blockade was then tested in human saphenous vein, using the pan-Cx inhibitor carbenoxolone (100 μM) or the specific Cx43 inhibiting peptide 43 Gap26 (200 μM) [ 30 , 31 ]. Both strategies reduced the development of IH ( Fig 10 ) and myointimal proliferation (PCNA staining) ( Fig 10 ) observed after 10 days of static culture, suggesting that Cx43 is the main Cx involved in VSMC proliferation and IH.…”
Section: Resultsmentioning
confidence: 99%